Association of microRNAs With Embryo Development and Fertilization in Women Undergoing Subfertility Treatments: A Pilot Study - Butler, Alexandra E.; Cunningham, Thomas Keith; Ramachandran, Vimal; Diboun, Ilhame; Halama, Anna; Sathyapalan, Thozhukat; Najafi-Shoushtari, S. Hani; Atkin, Stephen L. (Frontiers in Reproductive Health, 2021)
Objective. Small non-coding RNAs known as microRNAs(miRNAs) have emerging regulatory functions within the ovary that have been related to fertility. This study was undertaken to determine if circulating miRNAs reflect changes associated with parameters of embryo development and fertilization. Methods. In this cross-sectional pilot study, plasma miRNAs were collected from 48 sequentially presenting women, in the follicular phase prior to commencing in vitro fertilisation(IVF). Circulating miRNAs were measured using locked nucleic acid(LNA)-based quantitative polymerase chain reaction(qPCR) and an updated miRNA data set was used to determine their level of expression. Results. BMI and weight associated with miRNAs let7b-3p and miR-375, respectively (p<0.05), endometrium thickness at oocyte retrieval with miR-885-5p and miR-34a-5p (p<0.05), while miR-1260a was found to be inversely associated with anti-mullerian hormone(AMH;p=0.007). In addition, miR-365a-3p, miR122-5p and miR-34a-5p correlated with embryo fertilization rates (p<0.05); however, omitting cases of male infertility (n=15), miR122-5p remained significant (p<0.05) but miR-365a-3p and miR-34a-5p no longer differed, though interestingly miR1260a and mir93.3p became significant (p=0.0087/0.02 respectively). Age was negatively associated with miR-335-3p, miR-28-5p, miR-155-5p, miR-501-3p and miR-497-5p(p<0.05). Live birth rate was negatively associated with miR-335-3p, miR-100-5p, miR-497-5p, let-7d and miR-574-3p(p<0.05), but these were not significant when age was accounted for; however, with the exclusion of male factor infertility, all those miRNAs were no longer significant, though miR.150.5p emerged as significant (p=0.042). A beta regression model identified miR-1260a, miR-486-5p and miR-132-3p (p<0.03,p=0.0003,p<0.00001, respectively) as most predictive for fertilisation rate. Notably, changes in detectable miRNAs were not linked to cleavage rate, top quality embryos(G3D3), blastocyst or antral follicle count. Ingenuity pathway analysis showed that miRNAs associated with age were also associated with variables found in reproductive system disease. Conclusion. Plasma miRNA prior to the IVF cycle were associated with differing demographic and IVF parameters including age and may be predictive biomarkers of fertilisation rate.